There Is Any Effect Of Board Games For Teaching Reading Second Grade At Junior High School: Ada Pengaruh Board Games Terhadap Pembelajaran Membaca Kelas Dua SMP - Hanindya Navita Rahma; Yuli Astutik (Universitas Muhammadiyah Sidoarjo, 2022)
Game is one of the supporting media in classroom learning. In general, learning media refers to everything that is used to convey messages from the sender of the message to the recipient of the message that can increase or develop the horizons of thinking, feeling, and learning interest of students or students. The purpose of this study was to determine the effect of board game learning media in the classroom when applied as a support for continuous learning. This research was conducted in class VIII SMP PGRI 8 Sidoarjo. The findings of this study use quantitative methods, there are two instruments used by researchers, namely the results of the LKS taken twice. For this reason, the use of board games learning media can help teachers and students to facilitate access to learning media assistance in the form of board game media.